A history of antimicrobial drugs in animals: Evolution and revolution. Issue 2 (29th July 2020) - Lees, Peter; Pelligand, Ludovic; Giraud, Etienne; Toutain, Pierre‐Louis
Abstract: The evolutionary process of antimicrobial drug (AMD) uses in animals over a mere eight decades (1940–2020) has led to a revolutionary outcome, and both evolution and revolution are ongoing, with reports on a range of uses, misuses and abuses escalating logarithmically. As well as veterinary therapeutic perspectives (efficacy, safety, host toxicity, residues, selection of drug, determination of dose and measurement of outcome in treating animal diseases), there are also broader, nontherapeutic uses, some of which have been abandoned, whilst others hopefully will soon be discontinued, at least in more developed countries. Although AMD uses for treatment of animal diseases will continue, it must: (a) be sustainable within the One Health paradigm; and (b) devolve into more prudent, rationally based therapeutic uses. As this review on AMDs is published in a Journal of Pharmacology and Therapeutics, its scope has been made broader than most recent reviews in this field. Many reviews have focused on negative aspects of AMD actions and uses, especially on the question of antimicrobial resistance. This review recognizes these concerns but also emphasizes the many positive aspects deriving from the use of AMDs, including the major research‐based advances underlying both the prudent and rational use of AMDs. It is structured in seven sections: (1) Introduction; (2) Sulfonamide history; (3) Nontherapeutic and empirical uses of AMDs (roles of agronomists and veterinarians); (4) Rational uses of AMDs (roles of pharmacologists, clinicians, industry and regulatory controls); (5) Prudent use (residue monitoring, antimicrobial resistance); (6) International and inter‐disciplinary actions; and (7) Conclusions.